Aspectos imunogeneticos na pesquisa da etiologia da catarata senil - Massato Hida, M. (My University, 1978)
The immunogenetic study of senile cataract showed that the association with the HLA antigens and Ia antigens suggests an influence of the antigenicity for cataractogenesis, but not a peculiar specificity. However, the investigation of the immunoglobulins in lens suggest that the lens pathology may be produced by antibodies reacting with the lens capsule and consequently interfering with the lens epithelial metabolism, and contributes to the complex mechanism of cataract formation.
Immunogenetical study of senile cataract
Keywords: immunoglobulin; cataractogenesis; heredity; HLA system; immunogenetics; normal human; senile cataract; visual system